Lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material as well as preparation method and application thereof
The preparation of lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material through step-by-step ball milling process solves the problems of complex existing processes and poor material performance, achieves a combination of high energy density, good cycle performance and safety performance, and simplifies the process flow.
Patent Information
- Application Number
- CN202411907734.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-01
AI Technical Summary
The existing lithium manganese iron phosphate-lithium-rich manganese-based materials have complex preparation processes, poor material performance, and difficult to achieve commercial application.
Using a step-by-step ball milling process, a composite positive electrode material containing a carbon cladding is formed by mixing lithium manganese iron phosphate, lithium-rich manganese-based materials and carbon sources, simplifying the process flow and improving material performance.
The particle size of the positive electrode material is reduced, the diffusion distance of lithium ions is reduced, the conductivity and electrochemical properties of the material are improved, and the high energy density, good cycling performance and safety performance are combined, which simplifies the process flow and reduces production costs.
Smart Images

Figure CN119742335A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material, a preparation method thereof, and applications thereof. Background Art
[0002] Lithium iron phosphate batteries are widely used in power, 3C and energy storage fields due to their high safety, long cycle, low cost and environmental friendliness, and have become one of the most successful lithium batteries. Due to the limitations of lithium iron phosphate cathode materials (low specific capacity of only 170mAh / g), the improvement of the energy density of lithium iron phosphate batteries faces huge challenges.
[0003] Among them, lithium manganese iron phosphate (LMFP) material has the same olivine crystal structure as lithium iron phosphate (LFP) material, and due to Mn 2+ / Mn 3+ (4.1V vs.Li / Li + ) relative to Fe 2+ / Fe 3+ (3.7V vs.Li / Li + ) has a higher voltage window, and the comprehensive energy density can be increased by 10-20%. Compared with elements such as nickel, cobalt and zinc, manganese has the advantages of high reserves and low cost, and is regarded as one of the best choices for the next generation of lithium-ion battery positive electrode materials. However, the existence of the John-Teller effect (Mn during charging) 3+ Easily disproportionate to Mn 2+ , causing structural changes) resulting in poor cycle performance and difficulty in using it alone.
[0004] CN115939360A provides a liquid phase process for preparing a double-layer manganese iron phosphate-lithium-rich manganese-based / C composite positive electrode material, which effectively improves the manganese dissolution problem in the lithium manganese iron phosphate positive electrode material and improves the stability of the material, but has disadvantages such as complex preparation process and high cost.
[0005] With the widespread application of lithium batteries, the market has put forward higher requirements on the performance of lithium batteries. It is of great significance to develop a simple, efficient and commercially applicable lithium iron manganese phosphate positive electrode material. Summary of the invention
[0006] The main purpose of the present invention is to provide a lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material, a preparation method and application thereof, so as to solve the problems in the prior art that the preparation process of lithium iron manganese phosphate-lithium-rich manganese-based materials is complex, the material performance is poor, and further improvement is needed.
[0007] In order to achieve the above-mentioned purpose, according to one aspect of the present invention, a preparation method of a lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material is provided, wherein the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material comprises a mixed inner layer and a carbon coating layer coated on the surface of the mixed inner layer, and the mixed inner layer is a mixture of lithium iron manganese phosphate and lithium-rich manganese-based materials; the preparation method comprises the following steps: step S1, mixing lithium iron manganese phosphate, lithium-rich manganese-based materials and dispersants to obtain a mixed raw material, and wet-milling the mixed raw material to obtain a composite; step S2, drying the composite in an inert atmosphere or a reducing atmosphere to obtain a solid powder; step S3, mixing the solid powder with a carbon source, and dry-milling the mixture to obtain the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material.
[0008] Furthermore, in step S1, the ball-to-material ratio of wet ball milling is (1-10):1, the rotation speed is 200-600 rpm, and the time is 5-18 hours; preferably, the time of wet ball milling is 5-12 hours.
[0009] Furthermore, in step S3, the ball-to-material ratio of dry ball milling is (1-10):1, the rotation speed is 200-600 rpm, and the time is 0.5-18 h; preferably, the time of dry ball milling is 0.5-2 h.
[0010] Furthermore, the dispersant includes ethanol and / or water; and / or the solid content of the mixed raw material is 30-80%, preferably 40-70%; and / or the carbon source includes one or more of artificial graphite, graphene and carbon nanotubes.
[0011] Furthermore, taking the sum of the weight of lithium iron manganese phosphate, lithium-rich manganese-based materials and carbon sources as 100%, lithium iron manganese phosphate accounts for 40-88%, lithium-rich manganese-based materials account for 10-55%, and carbon sources account for 0.01-7%; preferably, lithium iron manganese phosphate accounts for 58-74%, lithium-rich manganese-based materials account for 25-40%, and carbon sources account for 0.01-3%.
[0012] Furthermore, in step S2, the drying temperature is 100-110°C, and the drying is carried out under vacuum conditions with a vacuum value of -90±5Kpa; the inert atmosphere includes one or more of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere; the reducing atmosphere includes one or more of a hydrogen atmosphere, a carbon monoxide atmosphere, and a reducing carbon atmosphere.
[0013] According to another aspect of the present invention, there is provided a lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material obtained by the above-mentioned preparation method of the present invention.
[0014] Further, in the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material, by weight percentage, the lithium iron manganese phosphate accounts for 40-88%, the lithium-rich manganese-based material accounts for 10-55%, and the carbon coating accounts for 0.01-7%; preferably, by weight percentage, the lithium iron manganese phosphate accounts for 58-74%, the lithium-rich manganese-based material accounts for 25-40%, and the carbon coating accounts for 0.01-3%; and / or the lithium iron manganese phosphate is an olivine structure with a chemical formula of Li a Mn b Fe c (PO4) d , wherein 0.8<a<1.2, 0.8<b+c<1.05, 0.1<b÷c<9, 0.8<d<1.2; and / or the lithium-rich manganese-based material is a lamellar structure or a spinel structure, with a chemical formula of nLi2MnO3·(1-n)LiMO2, 0<n<0.7, and M includes one or more of Sc, Ti, V, Cr, Mn, Fe, Co, Ni, and Zn; the D50 of lithium iron manganese phosphate is 0.45~2μm, and the electronic conductivity is ≥10 -5 S / cm; and / or the particle size D50 of lithium iron manganese phosphate is less than the particle size D50 of the lithium-rich manganese-based material, and the difference is 0.5 to 4.0 μm.
[0015] According to another aspect of the present invention, a positive electrode plate is provided, comprising the above-mentioned lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material of the present invention.
[0016] According to another aspect of the present invention, a secondary battery is provided, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is the above-mentioned positive electrode sheet of the present invention.
[0017] The technical scheme of the present invention is applied, lithium iron manganese phosphate, lithium-rich manganese-based materials and carbon sources are used as raw materials, and a step-by-step ball milling process is adopted to prepare a composite positive electrode material containing lithium iron manganese phosphate-rich lithium manganese-based and coated with a carbon layer. The lithium iron manganese phosphate and the lithium-rich manganese-based materials are evenly dispersed, the carbon layer coating is stable, and the particles are evenly mixed. The step-by-step ball milling process can reduce the particle size of the positive electrode material, reduce the diffusion distance of lithium ions, better construct lithium ion channels, and improve the comprehensive performance of the lithium iron manganese phosphate battery. In addition, the coating of the carbon material is simple and uniform, which is conducive to enhancing the bonding between materials and improving electrical conductivity and electrochemical performance. The preparation method of the present invention does not require the use of a high-temperature sintering step. The material performance can be optimized through a step-by-step ball milling process, which simplifies the process flow, reduces the production cost, and the preparation process is simple and efficient, which is conducive to the commercial application of lithium iron manganese phosphate positive electrode materials. The lithium ion battery assembled with the positive electrode material of the present invention can have both high energy density, good cycle performance and safety performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0019] Figure 1 The preparation flow chart of Example 1 according to the present invention is shown;
[0020] Figure 2 A cross-sectional structural model diagram of a positive electrode material according to Example 1 of the present invention is shown;
[0021] Figure 3 shows a microscopic morphology of the positive electrode material according to Example 1 of the present invention;
[0022] Figure 4 Showing the charge and discharge specific capacity curves according to Examples 1 to 3 of the present invention;
[0023] Figure 5 Cyclic performance curves of Examples 1 to 6 according to the present invention and Comparative Examples 1 to 2 are shown.
[0024] The above drawings include the following reference numerals:
[0025] 1. Carbon coating layer; 2. Lithium-rich manganese-based material; 3. Lithium iron manganese phosphate. DETAILED DESCRIPTION
[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0027] As described in the background technology of the present invention, there are problems in the prior art that the preparation process of lithium iron manganese phosphate-lithium-rich manganese-based materials is complicated and the material performance is poor, which needs to be further improved. In order to solve the above problems, in a typical embodiment of the present invention, a preparation method of lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material is provided, and the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material includes a mixed inner layer and a carbon coating layer coated on the surface of the mixed inner layer, and the mixed inner layer is a mixture of lithium iron manganese phosphate and lithium-rich manganese-based materials; the preparation method includes the following steps: step S1, mixing lithium iron manganese phosphate, lithium-rich manganese-based materials and dispersants to obtain a mixed raw material, and wet-milling the mixed raw material to obtain a composite; step S2, drying the composite in an inert atmosphere or a reducing atmosphere to obtain a solid powder; step S3, mixing the solid powder with a carbon source, and dry-milling to obtain a lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material.
[0028] Specifically, lithium iron manganese phosphate, lithium-rich manganese-based materials and dispersants are first mixed to obtain a mixed raw material, and the mixed raw material is wet-ball-milled to obtain a composite, that is, an inner layer of a mixture of lithium iron manganese phosphate and lithium-rich manganese-based materials. At the beginning of ball milling, the particles of lithium iron manganese phosphate and lithium-rich manganese-based materials are large and uneven. As the ball milling continues, the particles are gradually refined, the particle size becomes smaller, and the distribution becomes uniform; as the ball milling time is further extended, the particle size gradually reaches a relatively stable state. The mechanical force generated during the ball milling process will act on the lithium-rich manganese-based material, reduce its particle size, increase the specific surface area and produce more fresh interfaces, thereby increasing the contact area between the active substances. At the same time, the surface free energy of the material decreases, and Li + The migration path of Li + The activation energy of migration is reduced. The lithium manganese iron phosphate and lithium-rich manganese-based material composite is evenly dispersed, and the particle size of the lithium-rich manganese-based material is reduced, which can also further improve the compaction density of the positive electrode sheet.
[0029] The composite is then dried in an inert atmosphere or a reducing atmosphere to prevent the divalent Mn and Fe in the material from being oxidized to a trivalent state, thereby obtaining a solid powder. Finally, the solid powder is mixed with a carbon source and dry-milled, so that the coating of the carbon material is simpler and more uniform, and it is also beneficial to enhance the bonding of the amorphous carbon network between the lithium iron manganese phosphate and the lithium-rich manganese-based material, thereby obtaining the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material of the present invention.
[0030] It should be noted that conventional preparation methods generally require high-temperature sintering, which is to heat the powder or granular material to a temperature below its melting point to cause material migration and bonding between adjacent particles, thereby forming a dense whole, in order to reconstruct the crystal structure. However, the crystal structures of the lithium manganese iron phosphate and the lithium-rich manganese-based material of the present invention are significantly different. In the positive electrode mixed system, carbon mainly plays a conductive role, and dry ball milling in a carbon source environment is to supplement the carbon source required for the new interface generated by ball milling and reduce powder resistance. Therefore, after adding the carbon source and dry ball milling, the present invention can achieve relatively good cycle performance of the positive electrode material without high-temperature sintering, and the preparation process is significantly simplified.
[0031] The present invention uses lithium iron manganese phosphate, lithium-rich manganese-based materials and carbon sources as raw materials, adopts a step-by-step ball milling process, and prepares a composite positive electrode material containing lithium iron manganese phosphate-rich lithium manganese-based and coated with a carbon layer. The lithium iron manganese phosphate and the lithium-rich manganese-based materials are evenly dispersed, the carbon layer coating is stable, and the particles are evenly mixed. The step-by-step ball milling process can reduce the particle size of the positive electrode material, reduce the diffusion distance of lithium ions, better construct lithium ion channels, and improve the comprehensive performance of the lithium iron manganese phosphate battery. In addition, the coating of the carbon material is simple and uniform, which is conducive to enhancing the bonding between materials and improving electrical conductivity and electrochemical performance. The preparation method of the present invention does not require the use of a high-temperature sintering step, and the material performance can be optimized by a step-by-step ball milling process, which simplifies the process flow, reduces the production cost, and the preparation process is simple and efficient, which is conducive to the commercial application of lithium iron manganese phosphate positive electrode materials. The lithium ion battery assembled with the positive electrode material of the present invention can have high energy density, good cycle performance and safety performance. In addition, the step-by-step ball milling process of the present invention is simple and efficient, and the adjustability of the preparation process factors such as the size, direction and frequency of the external force is high, simple and convenient.
[0032] In order to make the ball-to-material ratio more consistent with the movement law of the ball milling medium, further improve the material fluidity and viscosity, improve the operating efficiency, reduce the cost, and better meet the product requirements, in a preferred embodiment, in step S1, the ball-to-material ratio of the wet ball milling is (1-10):1, the rotation speed is 200-600rpm, and the time is 5-18h; preferably, the wet ball milling time is 5-12h. The above ball milling speed and ball milling time help to accelerate the deformation and dispersion process of the powder particles, and further reduce the excessive crushing and cold welding of the powder particles, which is more conducive to the uniform dispersion of the particles, and at the same time it is also conducive to reducing the excessive refinement of the particles and the agglomeration caused by it, so that the particle size is reduced and the dispersibility is improved.
[0033] Based on similar reasons, in a preferred embodiment, in step S3, the ball-to-material ratio of dry ball milling is (1-10):1, the rotation speed is 200-600 rpm, and the time is 0.5-18 h; preferably, the time of dry ball milling is 0.5-2 h, which is more conducive to replenishing the carbon source required for the new interface produced by ball milling and further reducing the powder resistance.
[0034] In a preferred embodiment, the dispersant includes ethanol and / or water; and / or the solid content of the mixed raw material is 30-80%, preferably 40-70%; and / or the carbon source includes one or more of artificial graphite, graphene and carbon nanotubes. The solid content of the mixed raw material within the above range can further improve the fluidity and viscosity of the material.
[0035] The above-mentioned carbon sources are more suitable for coating using the step-by-step ball milling method of the present invention. Specifically, artificial graphite is relatively consistent in morphology and particle size distribution, has high carbon content, low volatile matter, very stable physical and chemical properties, low hardness, high porosity, low thermal conductivity, relatively balanced performance, good cycle performance, and good compatibility with electrolytes. Compared with other materials, artificial graphite has better cycle performance, high rate charge and discharge efficiency, and electrolyte compatibility. Graphene is a two-dimensional crystal composed of a single layer of carbon atoms tightly arranged, with excellent material properties such as super conductivity, good thermal conductivity, light transmittance, solubility, permeability, high flexibility and high strength. The high conductivity of graphene can further improve the charge and discharge speed and energy density of the battery, while its high flexibility and high strength can improve the stability and safety of the battery. Carbon nanotubes are one-dimensional nanomaterials with a special crystal structure. Their crystal structure is almost similar to the nuclear atomic arrangement of graphite and diamond. They have the characteristics of light weight, high strength and excellent conductivity, which are beneficial to further improve the energy density of lithium batteries, achieve fast charging and discharging, and increase cycle life.
[0036] In a preferred embodiment, the sum of the weights of lithium manganese iron phosphate, lithium-rich manganese-based materials and carbon sources is 100%, lithium manganese iron phosphate accounts for 40-88%, lithium-rich manganese-based materials account for 10-55%, and carbon sources account for 0.01-7%. The weight proportion of lithium manganese iron phosphate (LMFP) within the above range is more conducive to making the material have a higher energy density, can provide a more stable lithium ion diffusion path, and its higher voltage platform helps to improve the overall energy output of the battery. The weight proportion of lithium manganese-rich material (LRO) within the above range can further increase the specific capacity of the material, especially maintain good electrochemical properties under high charge state, thereby enhancing the cycle stability and energy density of the battery. The proportion of carbon source within the above range is more conducive to providing a suitable conductive network, reducing material impedance, and participating in the interface reconstruction during mechanical ball milling, which helps to form a uniform carbon coating layer, improve ion transfer efficiency and contact between materials, thereby improving the cycle performance of the battery.
[0037] Based on similar reasons, it is further preferred that lithium manganese iron phosphate accounts for 58-74%, lithium-rich manganese-based materials account for 25-40%, and carbon sources account for 0.01-3%. The above-mentioned specific ratio of LMFP and LRO helps to form a more uniform mixture during the ball milling process, and the above-mentioned addition amount of the carbon source is conducive to improving the quality of the carbon coating layer after ball milling, and is more conducive to the step-by-step ball milling process of the present invention, avoiding the need for subsequent high-temperature sintering, and simplifying the overall process. In addition, the low proportion of carbon source used can also help reduce the agglomeration phenomenon during the carbon coating process, further optimize the dispersion of the material and the construction of the conductive network, and ultimately make the prepared positive electrode material perform well in the charge and discharge cycle, with high energy density, good cycle performance and excellent safety performance, meeting the high requirements of lithium battery applications.
[0038] The appropriate drying temperature is conducive to the effective evaporation of the dispersant, and at the same time, the thermal stability of the material is maintained to avoid oxidation of Mn and Fe elements at high temperatures, so as not to destroy the crystal structure of the material, thereby maintaining the electrochemical activity and cycle performance of lithium iron manganese phosphate and lithium-rich manganese-based materials. Therefore, in a preferred embodiment, in step S2, the drying temperature is 100-110°C, and the drying is carried out under vacuum conditions, and the vacuum value is -90±5Kpa; the inert atmosphere includes one or more of a nitrogen atmosphere, an argon atmosphere, and a helium atmosphere; the reducing atmosphere includes one or more of a hydrogen atmosphere, a carbon monoxide atmosphere, and a reducing carbon atmosphere. Drying in the above-mentioned inert atmosphere or reducing atmosphere can further protect the material from the influence of oxygen and moisture in the air, prevent oxidation reactions and moisture adsorption, help maintain the metal elements in the material in a lower valence state, enhance the electronic conductivity of the material, and reduce internal impedance, thereby improving the safety, energy density and cycle performance of the battery.
[0039] In another typical embodiment of the present invention, a lithium iron manganese phosphate-rich lithium manganese-based positive electrode material is provided, which is obtained by the above-mentioned preparation method of the present invention. Due to the use of the step-by-step ball milling process of the present invention, it has a significantly simplified process flow and can have high energy density, good cycle performance and safety performance.
[0040] Based on similar reasons to the above, in a preferred embodiment, in the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material, by weight percentage, the lithium iron manganese phosphate accounts for 40-88%, the lithium-rich manganese-based material accounts for 10-55%, and the carbon coating accounts for 0.01-7%; preferably, by weight percentage, the lithium iron manganese phosphate accounts for 58-74%, the lithium-rich manganese-based material accounts for 25-40%, and the carbon coating accounts for 0.01-3%; and / or the lithium iron manganese phosphate is an olivine structure with a chemical formula of Li a Mn b Fe c (PO4)d , wherein 0.8<a<1.2, 0.8<b+c<1.05, 0.1<b÷c<9, 0.8<d<1.2; and / or the lithium-rich manganese-based material is a lamellar structure or a spinel structure, with a chemical formula of nLi2MnO3·(1-n)LiMO2, 0<n<0.7, and M includes one or more of Sc, Ti, V, Cr, Mn, Fe, Co, Ni, and Zn; the D50 of lithium iron manganese phosphate is 0.45~2μm, and the electronic conductivity is ≥10 -5 S / cm; and / or the particle size D50 of lithium iron manganese phosphate is less than the particle size D50 of the lithium-rich manganese-based material, and the difference is 0.5-4.0 μm, preferably 0.5-1.0 μm. Among them, the lithium-rich manganese-based material (LRO) is preferably nLi2MnO3·(1-n)LiMnO2 (LMO).
[0041] The olivine structure of lithium manganese iron phosphate has high stability. By limiting the chemical formula and element ratio within the above range, it can ensure that the material maintains a stable crystal structure during the charge and discharge process, thereby extending the service life of the battery. The doping of manganese elements can significantly increase the voltage platform of lithium iron phosphate, thereby improving the energy density of the material. At the same time, manganese and iron have similar chemical properties and can form a solid solution to maintain the electrochemical activity of the material. However, some Mn is easily dissolved during the cycle, and the cycle performance decreases. By adjusting the ratio of manganese and iron, the discharge specific capacity, rate performance and cycle performance of the material can be further optimized. In addition, lithium manganese iron phosphate inherits the high thermal stability and good safety performance of lithium iron phosphate. By limiting the chemical formula and element ratio within the above range, it can ensure that the material can remain safe and stable under harsh conditions, which helps to extend the service life of the battery and reduce the cost of replacing the battery. When the chemical formula and the ratio of each element of the lithium-rich manganese base are within the above range, the crystal structure of the material can be optimized, thereby improving its structural stability, specific capacity and cycle stability.
[0042] The D50 of lithium iron manganese phosphate within the above range is conducive to the uniform mixing of raw materials, which can make the material have a more suitable compaction density, thereby improving the overall energy density of the positive electrode material. At the same time, the appropriate particle size can reduce the influence of the Jan-Taylor effect on the manganese ions of the LMFP material, and it is not easy to cause particle breakage and manganese dissolution, thereby improving the cycle performance. Smaller particles are also conducive to the rapid transmission of lithium ions, thereby improving the low-temperature performance to a certain extent. The particle size of lithium iron manganese phosphate is smaller than that of lithium-rich manganese-based materials, which can further improve the ion diffusion performance. The smaller crystal size can also better alleviate the stress caused by volume change, thereby improving the ion diffusion performance and electrochemical performance of the material, and to a certain extent optimize the structural stability of the overall material, and reduce the structural mismatch problem caused by excessive particle size differences. By reasonably controlling the particle size relationship between lithium iron manganese phosphate and lithium-rich manganese-based materials, the electrochemical performance and cycle stability of the positive electrode material can be further optimized, thereby improving the energy density, charge and discharge speed and cycle life of the battery.
[0043] In another typical embodiment of the present invention, a positive electrode plate is also provided, comprising the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material of the present invention, which can have high energy density, good cycle performance and safety performance. The positive electrode plate can also include a conductive agent and a binder, the conductive agent includes one or more of carbon nanotubes, graphene, and acetylene black, and the binder includes one or more of polyvinylidene fluoride, polytetrafluoroethylene and polyacrylic acid.
[0044] In another typical embodiment of the present invention, a secondary battery is provided, including a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is the positive electrode sheet of the present invention. Since the lithium iron manganese phosphate-lithium-rich manganese-based-carbon-coated positive electrode material prepared by the step-by-step ball milling process of the present invention is used for assembly, the lithium ion battery can be cycled for 1200 cycles at room temperature 25°C and can be cycled for 700 cycles at high temperature 45°C, with significantly improved cycle performance.
[0045] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0046] Unless otherwise specified, the chemical formula of lithium manganese iron phosphate used in the following examples and comparative examples is LiFe 0.4 Mn 0.6 PO4, the chemical formula of lithium-rich manganese-based materials is 0.6Li2MnO3·0.4LiMnO2.
[0047] Example 1
[0048] Preparation flow chart see Figure 1 .
[0049] Step S1, adding 180g of lithium iron manganese phosphate raw material, 200g of lithium-rich manganese-based raw material and 267mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 64%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500rpm for 10h to obtain a composite;
[0050] Step S2, taking out the composite, drying it at 105° C. under a nitrogen atmosphere to obtain a solid powder;
[0051] Step S3, mixing the solid powder and graphene in a mass ratio of 97:3, loading into a planetary ball mill, with a ball-to-material ratio of 5:1, and dry ball milling at 300 rpm for 1 hour to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0052] Example 2
[0053] Step S1, adding 260 g of lithium iron manganese phosphate raw material, 120 g of lithium-rich manganese-based raw material and 267 mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 64%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500 rpm for 10 hours to obtain a composite;
[0054] Step S2, taking out the composite, drying it at 105° C. under a nitrogen atmosphere to obtain a solid powder;
[0055] Step S3, mixing the solid powder and graphene in a mass ratio of 97:3, loading into a planetary ball mill, with a ball-to-material ratio of 5:1, and dry ball milling at 300 rpm for 1 hour to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0056] Example 3
[0057] Step S1, adding 340 g of lithium iron manganese phosphate raw material, 40 g of lithium-rich manganese-based raw material and 267 mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 64%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500 rpm for 10 hours to obtain a composite;
[0058] Step S2, taking out the composite, drying it at 105° C. under a nitrogen atmosphere to obtain a solid powder;
[0059] Step S3, mixing the solid powder and graphene in a mass ratio of 97:3, loading into a planetary ball mill, with a ball-to-material ratio of 5:1, and dry ball milling at 300 rpm for 1 hour to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0060] Example 4
[0061] Step S1, adding 260 g of lithium iron manganese phosphate raw material, 120 g of lithium-rich manganese-based raw material and 267 mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 64%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500 rpm for 10 hours to obtain a composite;
[0062] Step S2, taking out the composite, drying it at 105° C. under a nitrogen atmosphere to obtain a solid powder;
[0063] Step S3, mixing the solid powder and carbon nanotubes in a mass ratio of 97:3, loading into a planetary ball mill with a ball-to-material ratio of 5:1, and dry ball milling at 300 rpm for 1 hour to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0064] Example 5
[0065] Step S1, adding 260 g of lithium iron manganese phosphate raw material, 120 g of lithium-rich manganese-based raw material and 267 mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 64%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500 rpm for 5 hours to obtain a composite;
[0066] Step S2, taking out the composite, drying it at 105° C. under a nitrogen atmosphere to obtain a solid powder;
[0067] Step S3, mixing the solid powder and graphene in a mass ratio of 97:3, loading into a planetary ball mill, with a ball-to-material ratio of 5:1, and dry ball milling at 300 rpm for 1 hour to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0068] Example 6
[0069] Step S1, adding 260 g of lithium iron manganese phosphate raw material, 120 g of lithium-rich manganese-based raw material and 267 mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 64%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500 rpm for 15 hours to obtain a composite;
[0070] Step S2, taking out the composite, drying it at 105° C. under a nitrogen atmosphere to obtain a solid powder;
[0071] Step S3, mixing the solid powder and graphene in a mass ratio of 97:3, loading into a planetary ball mill, with a ball-to-material ratio of 5:1, and dry ball milling at 300 rpm for 1 hour to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0072] Example 7
[0073] The difference from Example 2 is that, in step S1, 260 g of lithium iron manganese phosphate raw material, 120 g of lithium manganese-rich raw material and 200 mL of ethanol are added to a ball mill to obtain a mixed raw material (solid content of 71%), the ball-to-material ratio is 5:1, and the mixed raw material is wet-ball-milled at 500 rpm for 12 hours to obtain a composite.
[0074] Example 8
[0075] The difference from Example 2 is that, in step S1, 260 g of lithium manganese iron phosphate raw material, 120 g of lithium manganese-rich raw material and 700 mL of ethanol are added to a ball mill to obtain a mixed raw material (solid content is 41%), the ball-to-material ratio is 5:1, and the mixed raw material is wet-ball-milled at 500 rpm for 6 hours to obtain a composite.
[0076] Example 9
[0077] The difference from Example 2 is that, in step S3, the solid powder and graphene are mixed in a mass ratio of 97:3 and loaded into a planetary ball mill with a ball-to-material ratio of 5:1, and dry ball milled at 300 rpm for 2 h to obtain lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material.
[0078] Example 10
[0079] The difference from Example 2 is that, in step S3, the solid powder and graphene are mixed in a mass ratio of 97:3 and loaded into a planetary ball mill with a ball-to-material ratio of 5:1, and dry ball milled at 300 rpm for 1 hour to obtain lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material.
[0080] Embodiment 11
[0081] Step S1, adding 260g of lithium manganese iron phosphate raw material, 120g of lithium manganese-rich raw material and 120mL of ethanol into a ball mill to obtain a mixed raw material (solid content is 80%), the ball-to-material ratio is 1:1, and the mixed raw material is wet-milled at 200rpm for 18h to obtain a composite.
[0082] Step S2, taking out the composite, and drying it at 100° C. under a nitrogen atmosphere to obtain a solid powder.
[0083] Step S3, mixing the solid powder and artificial graphite in a mass ratio of 97:3, loading into a planetary ball mill with a ball-to-material ratio of 1:1, and dry ball milling at 200 rpm for 18 hours to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0084] Example 12
[0085] Step S1, adding 260g of lithium iron manganese phosphate raw material, 120g of lithium-rich manganese-based raw material and 1000mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 33%), the ball-to-material ratio is 10:1, and the mixed raw material is wet-ball milled at 600rpm for 5h to obtain a composite.
[0086] Step S2, taking out the composite, and drying it at 110° C. under a nitrogen atmosphere to obtain a solid powder.
[0087] Step S3, mixing the solid powder and carbon nanotubes in a mass ratio of 97:3, loading into a planetary ball mill, with a ball-to-material ratio of 10:1, and dry ball milling at 600 rpm for 0.5 h to obtain lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material.
[0088] Example 13
[0089] The difference from Example 2 is that
[0090] Step S1, adding 227 g of lithium iron manganese phosphate raw material, 157 g of lithium-rich manganese-based raw material and 267 mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 64%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500 rpm for 10 hours to obtain a composite;
[0091] Step S3, mixing the solid powder and graphene in a mass ratio of 98:2, loading into a planetary ball mill, with a ball-to-material ratio of 5:1, and dry ball milling at 300 rpm for 1 hour to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0092] Embodiment 14
[0093] The difference from Example 2 is that
[0094] Step S1, adding 290 g of lithium iron manganese phosphate raw material, 98 g of lithium-rich manganese-based raw material and 267 mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 64%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500 rpm for 10 hours to obtain a composite;
[0095] Step S3, mixing the solid powder and graphene in a mass ratio of 99:1, loading into a planetary ball mill, with a ball-to-material ratio of 5:1, and dry ball milling at 300 rpm for 1 hour to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0096] Embodiment 15
[0097] The difference from Example 2 is that
[0098] Step S1, adding 157 g of lithium iron manganese phosphate raw material, 215 g of lithium-rich manganese-based raw material and 267 mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 64%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500 rpm for 10 hours to obtain a composite;
[0099] Step S3, mixing the solid powder and graphene in a mass ratio of 95:5, loading into a planetary ball mill, with a ball-to-material ratio of 5:1, and dry ball milling at 300 rpm for 1 hour to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0100] Example 16
[0101] The difference from Example 2 is that
[0102] Step S1, adding 345 g of lithium iron manganese phosphate raw material, 39 g of lithium-rich manganese-based raw material and 267 mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 64%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500 rpm for 10 hours to obtain a composite;
[0103] Step S3, mixing the solid powder and graphene in a mass ratio of 98:2, loading into a planetary ball mill, with a ball-to-material ratio of 5:1, and dry ball milling at 300 rpm for 1 hour to obtain lithium manganese iron phosphate-lithium-rich manganese-based positive electrode material.
[0104] Comparative Example 1
[0105] Lithium manganese iron phosphate and graphene were mixed in a mass ratio of 97:3 and loaded into a planetary ball mill with a ball-to-material ratio of 5:1. They were dry-milled at 300 rpm for 1 hour to obtain a positive electrode material.
[0106] Comparative Example 2
[0107] 180g of lithium iron manganese phosphate material and 20g of nano-scale lithium-rich manganese-based material are added to a fusion machine, the speed is adjusted to 2000rpm, and the time is 10 minutes to obtain a first composite; 10g of the first composite and 5g of oleic acid are taken and stirred evenly to obtain a second mixture, and the second mixture is sent to a muffle furnace, heated to 500°C in an air atmosphere, kept warm for 4 hours, and then the temperature is lowered to room temperature and taken out to obtain a positive electrode material.
[0108] Comparative Example 3
[0109] Step S1, adding 260 g of lithium iron manganese phosphate raw material, 120 g of lithium-rich manganese-based raw material and 267 mL of ethanol into a ball mill to obtain a mixed raw material (solid content of 60%), with a ball-to-material ratio of 5:1, and wet-milling the mixed raw material at 500 rpm for 10 hours to obtain a composite;
[0110] Step S2, taking out the composite, drying it at 105° C. under a nitrogen atmosphere to obtain a solid powder;
[0111] Step S3, mixing the solid powder and graphene in a mass ratio of 97:3, feeding into a muffle furnace, heating to 500° C. in an air atmosphere, keeping the temperature for 4 hours, then cooling to room temperature and taking out to obtain a positive electrode material.
[0112] Performance Test:
[0113] (1) The material characteristics of the positive electrode materials prepared in the above examples and comparative examples were tested. The results are shown in Table 1.
[0114] Chemical formula and element proportion: Inductively coupled plasma-mass spectrometry (ICP-OES), tested in accordance with GB / T 33822-2017.
[0115] D50: Laser particle size analysis method, tested according to GB / T 33822-2017.
[0116] Electronic conductivity: Semiconductor powder resistivity test analysis method, tested in accordance with GB / T 33822-2017.
[0117] (2) The positive electrode materials prepared in the above-mentioned embodiments and comparative examples are mixed with acetylene black, PVDF and N-methylpyrrolidone to prepare a slurry, and the slurry is evenly coated on an aluminum foil to prepare a positive electrode sheet; ethylene carbonate and ethyl methyl carbonate are mixed in a volume ratio of 2:8 and LiFP6 is added to form an electrolyte; a lithium sheet is used as a negative electrode; and a lithium-ion battery is assembled.
[0118] The prepared lithium-ion battery was electrochemically tested using an electrochemical instrument (Shenzhen Xinweier Electrochemical Test Cabinet) at a temperature of 25°C and 45°C, respectively. The charge and discharge voltage was 2.5-4.4V, and the 1C / 1C test cycle performance was performed. The results are shown in Table 2.
[0119] Table 1
[0120]
[0121] Table 2
[0122]
[0123] The cross-sectional structure model diagram of the positive electrode material of Example 1 is shown in Figure 2 It can be seen that the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material of the present invention is a double-layer structure, including a mixed inner layer and a carbon coating layer 1 coated on the surface of the mixed inner layer, and the mixed inner layer is a mixture of lithium iron manganese phosphate 3 and lithium-rich manganese-based material 2.
[0124] The microscopic morphology (SEM photo) of the positive electrode material of Example 1 is shown in Figure 3 , combined with Figure 2It can be seen that the carbon layer is coated with disorderly arranged physical mixture of lithium manganese iron phosphate and lithium-rich manganese-based materials.
[0125] The charge and discharge specific capacity curves of Examples 1 to 3 are shown in Figure 4 ,It can be seen that the mixing of lithium-rich manganese-based is beneficial to smooth the transition region of the LMFP dual platform, which is beneficial to the preliminary judgment of battery capacity based on voltage in BMS.
[0126] The cycle performance curves (25°C, 1C / 1C, 80%) of Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Figure 5 The use of a blended positive electrode can improve the battery cycle performance, while optimizing the carbon source selection and carbon layer can enhance the material conductivity and thus improve the cycle performance.
[0127] It can be seen from the above that the increase in the amount of lithium iron manganese phosphate added is conducive to the improvement of cycle performance; the increase in the amount of lithium-rich manganese-based material added is conducive to improving the charge and discharge specific capacity. Compared with the comparative example, each embodiment of the present invention uses lithium iron manganese phosphate, lithium-rich manganese-based materials and carbon sources as raw materials, and adopts a step-by-step ball milling process to prepare a composite positive electrode material containing lithium iron manganese phosphate-rich lithium manganese and coated with a carbon layer. The lithium iron manganese phosphate and the lithium-rich manganese-based materials are evenly dispersed, the carbon layer coating is stable, and the particles are evenly mixed. The step-by-step ball milling process can reduce the particle size of the positive electrode material, reduce the diffusion distance of lithium ions, better construct lithium ion channels, and improve the comprehensive performance of lithium iron manganese phosphate batteries. The coating of carbon materials is simple and uniform, which is conducive to enhancing the bonding between materials and improving electrical conductivity and electrochemical properties. The preparation method of the present invention does not require the use of a high-temperature sintering step. The material performance can be optimized through a step-by-step ball milling process, which simplifies the process flow, reduces production costs, and the preparation process is simple and efficient, which is conducive to the commercial application of lithium iron manganese phosphate positive electrode materials. The lithium ion battery assembled with the positive electrode material of the present invention can have high energy density, good cycle performance and safety performance.
[0128] In addition, it can be seen that when each process parameter is within the preferred range of the present invention, the overall effect is better.
[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a lithium iron manganese phosphate-rich lithium manganese-based positive electrode material, characterized in that: The lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material comprises a mixed inner layer and a carbon coating layer coated on the surface of the mixed inner layer, wherein the mixed inner layer is a mixture of lithium iron manganese phosphate and lithium-rich manganese-based material; the preparation method comprises the following steps: Step S1, mixing lithium iron manganese phosphate, a lithium-rich manganese-based material and a dispersant to obtain a mixed raw material, and wet-ball milling the mixed raw material to obtain a composite; Step S2, drying the composite in an inert atmosphere or a reducing atmosphere to obtain a solid powder; Step S3, mixing the solid powder with a carbon source, and performing dry ball milling to obtain the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material.
2. The preparation method according to claim 1, characterized in that: In the step S1, The wet ball milling has a ball-to-material ratio of (1-10):1, a rotation speed of 200-600 rpm, and a time of 5-18 hours; Preferably, the wet ball milling time is 5 to 12 hours.
3. The preparation method according to claim 1 or 2, characterized in that: In the step S3, The ball-to-material ratio of the dry ball mill is (1-10):1, the rotation speed is 200-600 rpm, and the time is 0.5-18 hours; Preferably, the dry ball milling time is 0.5 to 2 hours.
4. The preparation method according to any one of claims 1 to 3, characterized in that The dispersant comprises ethanol and / or water; and / or The solid content of the mixed raw material is 30-80%, preferably 40-70%; and / or The carbon source includes one or more of artificial graphite, graphene and carbon nanotubes.
5. The preparation method according to any one of claims 1 to 4, characterized in that: Taking the sum of the weight of the lithium iron manganese phosphate, the lithium-rich manganese-based material and the carbon source as 100%, The lithium iron manganese phosphate accounts for 40-88%, the lithium-rich manganese-based material accounts for 10-55%, and the carbon source accounts for 0.01-7%; Preferably, the lithium iron manganese phosphate accounts for 58-74%, the lithium-rich manganese-based material accounts for 25-40%, and the carbon source accounts for 0.01-3%.
6. The preparation method according to any one of claims 1 to 5, characterized in that In step S2, the drying temperature is 100-110° C., and the drying is performed under vacuum conditions with a vacuum value of -90±5Kpa; The inert atmosphere includes one or more of a nitrogen atmosphere, an argon atmosphere and a helium atmosphere; The reducing atmosphere includes one or more of a hydrogen atmosphere, a carbon monoxide atmosphere and a reducing carbon atmosphere.
7. A lithium iron manganese phosphate-rich lithium manganese-based positive electrode material, characterized in that: Obtained by the preparation method according to any one of claims 1 to 6.
8. The lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material according to claim 7, characterized in that: In the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material, In terms of weight percentage, the lithium iron manganese phosphate accounts for 40-88%, the lithium-rich manganese-based material accounts for 10-55%, and the carbon coating accounts for 0.01-7%; preferably, in terms of weight percentage, the lithium iron manganese phosphate accounts for 58-74%, the lithium-rich manganese-based material accounts for 25-40%, and the carbon coating accounts for 0.01-3%; and / or The lithium manganese iron phosphate has an olivine structure and a chemical formula of Li a Mn b Fe c (PO4) d , where 0.8<a<1.2, 0.8<b+c<1.05, 0.1<b÷c<9, 0.8<d<1.2; and / or The lithium-rich manganese-based material has a lamellar structure or a spinel structure, and the chemical formula is nLi2MnO3·(1-n)LiMO2, 0<n<0.7, and M includes one or more of Sc, Ti, V, Cr, Mn, Fe, Co, Ni, and Zn; The D50 of the lithium manganese iron phosphate is 0.45-2 μm, and the electronic conductivity is ≥10 -5 S / cm; and / or The particle size D50 of the lithium iron manganese phosphate is less than the particle size D50 of the lithium-rich manganese-based material, and the difference is 0.5 to 4.0 μm.
9. A positive electrode sheet, characterized in that: It includes the lithium iron manganese phosphate-lithium-rich manganese-based positive electrode material as described in claim 7 or 8.
10. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, characterized in that: The positive electrode sheet is the positive electrode sheet according to claim 9.
Citation Information
Patent Citations
Composite lithium-rich manganese-based cathode material for lithium ion battery and preparation method
CN107887594A
Carbon-coated composite negative active material comprising lithium iron phosphate, preparation method of composite negative active material and application in lithium ion battery negative electrode
CN110233246A
Lithium ion battery positive electrode composite material and preparation method and application thereof
CN114512655A
Battery positive electrode material and application thereof
CN115863620A
Lithium manganese iron phosphate-lithium-rich manganese-based composite positive electrode material, preparation method and application
CN115939360A